Risk Factors for Invasive Aspergillosis in Patients Admitted to the Intensive Care Unit With Coronavirus Disease 2019: A Multicenter Retrospective Study - Xu, Jiqian; Yang, Xiaobo; Lv, Zheng; Zhou, Ting; Liu, Hong; Zou, Xiaojing; Cao, Fengsheng; Zhang, Lu; Liu, Boyi; Chen, Wei; Yu, Yuan; Shu, Huaqing; et al. (Frontiers in Medicine, 2021)
Background: Invasive pulmonary aspergillosis (IPA) is a life-threatening complication in coronavirus disease 2019 (COVID-19) patients admitted to intensive care units (ICUs), but risk factors for COVID-19-associated IPA (CAPA) have not been fully characterized. The aim of the current study was to identify factors associated with CAPA, and assess long-term mortality. Methods: A retrospective cohort study of adult COVID-19 patients admitted to ICUs from six hospitals was conducted in Hubei, China. CAPA was diagnosed via composite clinical criteria. Demographic information, clinical variables, and 180-day outcomes after the diagnosis of CAPA were analyzed. Results: Of 335 critically ill patients with COVID-19, 78 (23.3%) developed CAPA within a median of 20.5 days (range 13.0–42.0 days) after symptom onset. Compared to those without CAPA, CAPA patients were more likely to have thrombocytopenia (50% vs. 19.5%, p < 0.001) and secondary bacterial infection prior to being diagnosed with CAPA (15.4% vs. 6.2%, p = 0.013), and to receive vasopressors (37.2% vs. 8.6%, p < 0.001), higher steroid dosages (53.9% vs. 34.2%, p = 0.002), renal replacement therapy (37.2% vs. 13.6%, p < 0.001), and invasive mechanical ventilation (57.7% vs. 35.8%, p < 0.001). In multivariate analysis incorporating hazard ratios (HRs) and confidence intervals (CIs), thrombocytopenia (HR 1.98, 95% CI 1.16–3.37, p = 0.012), vasopressor use (HR 3.57, 95% CI 1.80–7.06, p < 0.001), and methylprednisolone use at a daily dose ≥ 40 mg (HR 1.69, 95% CI 1.02–2.79, p = 1.02–2.79) before CAPA diagnosis were independently associated with CAPA. Patients with CAPA had longer median ICU stays (17 days vs. 12 days, p = 0.007], and higher 180-day mortality (65.4% vs. 33.5%, p < 0.001) than those without CAPA. Conclusions: Thrombocytopenia, vasopressor use, and corticosteroid treatment were significantly associated with increased risk of incident IPA in COVID-19 patients admitted to ICUs. The occurrence of CAPA may increase the likelihood of long-term COVID-19 mortality.